Measurement copper and zinc in Al Shamia City soilSelected by usingjacson method - Amer Yassir Kadhim (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper , the limitedconcentrationcopper (Cu) and zinc (Zn) were measuredin Soils Selected frommain and brunch streets of Shamia city inQadisiaprovince . The measurements were done by Atomic Absorption Spectrometerusing jacson method. We find the maximum value ofconcentration copper was (123.48)ppm in pattern no. (3) and minimum (17.77)ppm in pattern no. (8) with average (52.18)ppm and the zinc the maximum value was (127.42)ppm in pattern no. (8) and the minimum was (27.17)ppm in pattern (4) with average (78.89)ppmThe results are shown in tables and figures ..